The Effects of Parental Behavior on Adolescent Social Development - Kaliwal, Asadullah (Journal of Social Sciences - Kabul University, 2022)
This study is a descriptive-applied research aimed at elucidating the effects of parental behavior on the social development of adolescents. The study analyzes existing research and provides answers to the research question. The findings indicate that adolescents raised by authoritarian parents struggle with achieving independence, and such parental behavior increases the likelihood of juvenile delinquency, deviance, and misbehavior. Adolescents with overly permissive parents tend to lack commitment to values and face confusion and a lack of planning. Conversely, adolescents raised by democratic parents develop mutual respect, gradually gain independence, and experience progressive social development as they age. Additionally, adolescents with overprotective parents often exhibit rudeness, selfishness, and a sense of entitlement. The study concludes that appropriate parental behavior plays a crucial role in fostering healthy social development in adolescents.